CGFU-PM 515 based physical education learning model to improve forward roll skills in elementary school students in Sleman Regency - Ari Iswanto; Rezha Arzhan Hidayat; Fathan Nurcahyo; Hary Widodo; Muhammad Wahyu Arga (Jorpres (Jurnal Olahraga Prestasi), 2025)
This study aims to examine the physical education learning model based on CGFU PM-515 on improving forward roll skills in elementary school students in Sleman Regency. The method used is quasi-experimental with a one-group pretest-posttest design. The research subjects were 117 students from four elementary schools, namely SD Negeri Condongcatur, SD Muhammadiyah Condongcatur, SD Negeri Deresan, and SD Negeri Percobaan 2. Data collection techniques were carried out through skill tests, knowledge tests, and attitude questionnaires. Data analysis began with normality and homogeneity tests, followed by the Wilcoxon Signed Ranks Test due to non-normally distributed data and partially non-homogeneous data. The results showed a significant difference between pretest and posttest scores in the variables of skills, knowledge, and attitude with a significance value of 0.000 < 0.05. These results prove that the implementation of the CGFU PM-515-based physical education learning model has a significant impact on improving forward roll skills in elementary school students. Thus, the CGFU PM-515 learning model can be used as an effective and innovative alternative learning model for physical education in elementary schools.